Climate Afflictions - Mahmud, Iffat; Raza, Wameq A.; Hossain, Md Rafi (Washington, DC: World Bank, 2021)
Bangladesh’s vulnerability to the effects of climate change is well documented; the evidence on the direct relationship between climate change and health focusing on Bangladesh is less so. Global evidence suggests intensification of climate change will increase incidences and variations of infectious diseases. Climate Afflictions contributes to filling this important knowledge gap. It includes a systematic review of existing literature on the relationship between climate change and health, distinguishing between climate change and variability. It establishes the relationship between climate variability and infectious diseases and mental health using household-level data. It also documents changes in climate patterns in Bangladesh over the past 44 years using monthly meteorological data. Overall, the report finds a strong relationship between infectious diseases, mental health, and climate variability. Based on analyses of primary data, it concludes that the prevalence of vector-borne diseases is higher during the monsoon than dry seasons, while the opposite is true for waterborne illnesses. Meanwhile, rising humidity and mean temperature are positively associated with respiratory illnesses. In terms of mental health conditions, while temperature is negatively correlated to depression, anxiety among individuals is likely to increase with temperature and humidity. Irrespective of the season, morbidity and mental health issues are highest in densely populated urban hubs such as Dhaka and Chattogram compared to other areas. The mean temperature in Bangladesh has increased by 0.5°C between 1976 and 2019. Overall, summers are becoming hotter and longer, the monsoon season is extending, and winters are becoming warmer. Consequently, Bangladesh is on the path to losing its distinct seasonality. With global warming progressing faster than initially projected, stresses on human health may be elevated to an extent that can overburden the systems to a point at which adaptation will no longer be possible. Countries susceptible to climate change, like Bangladesh, need to be better prepared.